Position on how to spend leisure time sports activities for the Veterans and Disabled - M. Kiani; T. Shirvani; H. Ghanbari; S. Kiani (Afarand Scholarly Publishing Institute, 2013)
Introduction: Time, the most valuable human asset to the constructive expression of human life, Therefore desirable to identify ways for the Disabled and explain its impact on leisure, health and happiness, they also develop cultural, social and educational imperative and important this issue is proven ones. Purpose: This study aimed to determine the manner of leisure sports activities the Disabled Athlete in the province of Charmohal and Bakhtiyari and its relationship with some of the factors was performed. Materials and Methods: Study was a descriptive field and 167 of the Disabled athletes (male and female) were selected as research samples and the questionnaires that made this area And the validity and reliability with Cronbachchr('39')s alpha test (0.81= α) And surveys of professionals and physical education teachers had been approved, responded. In order to describe the characteristics of research subjects and variables, Data using descriptive statistics and inferential statistics, including Friedman, chi-square method (K2) «xi two" were analyzed. Results & Conclusion: Results showed that 73/63% of samples had full health. Disabled major leisure practices to watch TV, read books and newspapers as well as worship and Desirable and sports. The main research activity samples, respectively, hiking, swimming, climbing, chess was dedicated. Also, business vitality and joy, the positive effects of exercise, to maintain the operating health of the exercise was the main trend samples. The results suggest that it was between sex, marriage and celibacy, Health and Leisure with the amount of monthly income for the Disabled There is a significant relationship at α = 1%, While between gender, health, income and marital monthly sports activities addressing significant relationship was observed at α = 1%. Study indicates that most examples of research that physical activity during leisure to enjoy optimal health of body and spirit, and improve their social relations are. And if access to sports facilities, among other activities to address their priorities as the sporting activities and courses on other disciplines prefer walking and swimming.